Identification of Cryptosporidium in goats by 18S rRNA across four districts in Terengganu, Malaysia - Barudin, Mohd Aiman; Mat Yusof, Afzan (2016)
The research aimed to access the first distribution and genotypes of Cryptosporidium spp. using molecular tools in Malaysian goats from four farms in Terengganu. Methodology and results: A total of 454 goat faecal specimens were randomly collected from four selected farms located Kuala Terengganu, Setiu, Marang and Besut districts. Cryptosporidium spp. positive samples from the qualitative examination using combination of modified formalin-ether concentration technique (M-FECT) and modified Ziehl-Neelsen (MZN) staining were withheld for molecular characterization using nested PCR assay targeting the 18S rRNA gene. The 18S rRNA-based PCR successfully identified the predominance of zoonotic species of Cryptosporidium parvum among all studied samples. Conclusion, significance and impact of study: The genotyping study signified that goats should be considered as one of the most important reservoirs for Cryptosporidium parvum in the studied farms. It is suggested that there is the possibility of zoonotic and anthroponotic transmissions of asymptomatic cryptosporidiosis among the goats and animal handlers. Therefore, the need of further molecular subtyping of Cryptosporidium species/genotypes together with comprehensive sanitary monitoring by goat handlers are highly recommended to minimize the transmission of this parasite.